(untitled) (Revista Apotheke, 2019)
This work seeks to demonstrate and reflect on Drawing and its teaching since the comprehension of a Doctoral Research in Artistic Education at the University of Porto, Portugal, finalized in the year 2015. In addition, it discusses the research methods chosen in Art/Education Based on Visual Arts, in order to contextualize the appropriate methodological platforms for the presented problem. Focused and on the need to interpret what is to be "know how to draw" and "do not know how to draw", I bring some considerations from visual narratives in the logbook of that research, (re) looking at their own questions, questioning the discourses and practices disseminated in Visual Arts Teachers Education courses at the present time. By the end, I suggest a greater attention to the Drawing and its teaching in the Visual Arts Teachers Education in Brazil and Portugal.